SYMMETRIC POLYNOMIALS ON THE REAL BANACH SPACE L∞[0,1] - Василишин, Тарас Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We construct the algebraic basis of the algebra of all continuous symmetric polynomials on the real Banach space of all Lebesgue measurable essentially bounded functions on [0,1] .